Răspuns :
a+b=6335 ⇒ ca c egal cu 9655-6335
c=3320
b+c=7522 ⇒ ca a=9655-7522
a=2133
b=9655-(3320+2133)
b=9655-5453
b=4202
c=3320
b+c=7522 ⇒ ca a=9655-7522
a=2133
b=9655-(3320+2133)
b=9655-5453
b=4202
9655-7522=2133(a)
6335-2133=4202(b)
7522-4202=3320(c)
cum am făcut:din sumă am scăzut b+c și am aflat a.Din a+b am scăzut a și mi-a dat b.Din b+c am scăzut b și dă c.
6335-2133=4202(b)
7522-4202=3320(c)
cum am făcut:din sumă am scăzut b+c și am aflat a.Din a+b am scăzut a și mi-a dat b.Din b+c am scăzut b și dă c.